A NEW DIGITAL MUSIC ARCHIVING MODEL BASED ON A NEW COGNITIVE AND CONSTRUCTIVE LEARNING APPROACH - HAMZAH, HAMMUZAMER IRWAN (2016)
Digital music collection on a personal device may contain duplication records. Duplication of the digital music records may take place if there is no proper control of the storing I archiving operation